CORRELATION BETWEEN THE BEHAVIOR OF PERINEUM CARE AND THE EFFECTIVENESS OF PERINEAL WOUND HEALING INPOSTPARTUM MOTHERS : CORRELATION BETWEEN THE BEHAVIOR OF PERINEUM CARE (Wijaya Husada, 2020)
Of the effectiveness factors of perineal wound healing is the behavior of perineal care.Perineal care behavior is something that is done by a person to maintain the fulfillment of the need to make healthy areas between the thighs, vulva and rectum in the mother between the birth of the placenta until the return of genetic organs such as before pregnancy.This study is to analyze the magnitude of the relationship between the behavior of perineal care with the effectiveness of perineal wound healing in postpartum mothersDescriptive analytic with cross sectional research design The population of this study was puerperal mothers who suffered perineal injuries and 30 respondents obtained the sample size.This research was conducted in August 2019 in the Sindang Barang Health Center.This bivariate analyze used Kendal tau.from the bivariate analysis showed that there was a significant relationship between the behavior of perineal care (p = 0.010) and the effectiveness of perineal wound healing.Based on the results of univariate analysis, it was found that the behavior of perineal care was negative by 20 respondents (66.7%).And the effectiveness of healing perineal wounds in postpartum mothers obtained results of 15 respondents (50.0%) were not effective in healing perineal wounds and as many as 15 respondents (50.0%) were effective in healing their perineal wounds.In this study there was a significant relationship on the behavior variables of perineal care with the effectiveness of perieneum wound healing. And based on these results it is expected that the puerperal woman to pay attention to the perineal wound and control the behavior of perineal care.